Effect of low-pressure storage on the quality of green capsicums (Capsicum annum L.). Issue 5 (3rd September 2018) - Pristijono, Penta; Bowyer, Michael C.; Scarlett, Christopher J.; Vuong, Quan V.; Stathopoulos, Costas E.; Golding, John B.
ABSTRACT: Green capsicums ( Capsicum annum L .) were stored under low pressure (4 kPa) at 10°C for 5 and 11 days with 100% RH. The results showed that the incidence of stem decay under low-pressure storage for 5 and 11 days and storage at ambient atmosphere at 20°C for 3 days was lower compared to fruits that were stored at regular atmosphere at 10°C. Fruit that had been stored at low pressure at 10°C had no symptoms of flesh rots for up to 11 days, whilst fruit which had been stored at regular atmosphere at 10°C had 6% flesh rots after 11 days storage at 10°C.There was no difference in flesh firmness and colour retention between fruits stored at low pressure and regular pressure at 10°C. Capsicums stored at low pressure had higher overall acceptability compared to fruit that were stored at regular atmosphere at 10°C. These results demonstrate the potential of low pressure storage as an effective technique to manage capsicum fruit quality, however, there was no additional benefit when fruits were stored at low pressure for more than 5 days.